Penggunaan Adverbia Ichiou Dalam Novel Seri Reikan Kentei Dan Kiokuya Dilihat Dari Sudut Pandang â€œPartisipanâ€ - Tsaniatilwadai Anugrah Yudijanto (Janaru Saja Jurnal Program Studi Sastra Jepang, 2019)
Abstract: The purpose of this research is to find out the use of the ichiou adverb in the speech situations from participants with sociolinguistic approach. The method used in this research is descriptive method with qualitative analysis. Data sources are novels and questionnaires. The data collection of this study is choosing a sentence containing the ichiou adverb from six novels. Furthermore, these sentences were used as multiple-choice questionnaire containing the frequency of using ichiou adverb in some situations. As for some conclusions from the results of this research depend on the speech situation, social relations greatly influenced the use of the ichiou adverb only used for family, relatives or close friends. Keywords: Ichiou adverb, sociolinguistics, participant Abstrak: Tujuan dalam penelitian ini yakni untuk mengetahui penggunaan adverbia ichiou dalam beberapa situasi percakapan ditinjau dari penggunanya dengan pendekatan sosiolinguistik. Metode yang digunakan merupakan metode analisis kualitatif. Sumber data yang digunakan berasal dari novel dan angket , sedangkan data dikumpulkan berdasarkan percakapan yang terdapat dalam novel seri Reikan Kentei dan Kiokuya. Beberapa hasil analisis menunjukkan bahwa hubungan sosial memengaruhi penggunaan adverbia ichiou dalam suatu percakapan. Kata kunci: adverbia ichiou, sosiolinguistik, partisipan